High-precision prescribed-time path following for quadrotor. (21st April 2020) - Ding, Yibo; Wang, Xiaogang; Bai, Yuliang; Cui, Naigang
A high-precision prescribed-time guidance law is developed for a quadrotor to accomplish precise path following at predesigned time T . Firstly, a new control structure is proposed for a quadrotor to perform fixed-velocity back-to-turn flying mode by introducing four controllers, which can realize a non-sideslip and bank-to-turn flight scheme just like a fixed-wing unmanned aerial vehicle. Then, prescribed-time guidance law is presented based on fixed-velocity back-to-turn flying mode via combining sliding mode control with a compensation functionp t to improve tracking precision of conventional methods. Compensation functionp t is designed to make state error achieve convergence at prescribed time exactly. Meanwhile, global sliding mode is established to enhance robustness of the system. Then, the stability and characteristic of prescribed-time convergence are proved strictly. Finally, simulations with a 6-degree-of-freedom quadrotor model are carried out to demonstrate the effectiveness and superiority of prescribed-time guidance law by comparing with traditional guidance law.